2017
DOI: 10.4103/0366-6999.209900
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fertility Following Enucleation of Intramural Myomas in Infertile Women

Abstract: Background:The relationship between intramural myomas and fertility remains unclear. The main debate rests on whether cavity-distorting intramural myomas (CDMs) adversely affect fertility more than non-CDMs. We aimed to compare the effects of enucleating non-CDMs and CDMs on fertility improvement in females with unexplained infertility.Methods:We prospectively recruited 83 women undergoing myomectomy for unexplained infertility with intramural myomas between June 2008 and November 2012 and classified them into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Likewise, this review did not consider the position of fibroids due to the lack of data available. This is a factor which may have an impact on fertility, depending on whether the myoma is intramural or subserous, or if it is distorting the uterine cavity (Tian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, this review did not consider the position of fibroids due to the lack of data available. This is a factor which may have an impact on fertility, depending on whether the myoma is intramural or subserous, or if it is distorting the uterine cavity (Tian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies identified for this review focused on the impacts of the route of abdominal myomectomy on fertility (Table 5). Two other papers [9,20] performed secondary analyses related to surgical modality, and their findings are included in this topic section. We specifically examined the surgical techniques of laparotomic (also referred to in this review as open) and laparoscopic myomectomy.…”
Section: Routes Of Surgery and Laparoscope-assisted Devicesmentioning
confidence: 99%
“…Five articles incorporating data from 829 patients studied fertility after laparotomic vs laparoscopic myomectomy [9,20 −23], with inconsistent results regarding pregnancy rates by surgical route. One RCT (n = 131) found no difference in pregnancy rates on the basis of the route of surgery (laparotomic 56% vs laparoscopic 54%) [21], whereas 2 cohort studies showed a trend toward increased pregnancy rates among patients who received a laparoscopic approach [9,23], and another noted higher postoperative pregnancy rates among patients who underwent laparotomic myomectomy [20].…”
Section: Laparotomic Vs Laparoscopic Myomectomymentioning
confidence: 99%
See 1 more Smart Citation
“…In women with submucosal fibroids, myomectomy restores pregnancy rates to those similar of normal control patients (11). Similarly, a myomectomy in patients with intramural fibroids has been associated with higher pregnancy rates (5, 16, 17). In the future, less invasive therapies, such as targeted molecular therapy, may reduce the need for operative intervention.…”
Section: Fibroidsmentioning
confidence: 99%